Options for the revision of the multilateral system of access and benefit-sharing. A primer for multi-stakeholder consultations. Background context paper for PGR informal stakeholder workshop - Halewood, Michael (Food and Agriculture Organization of the United Nations, 2014)
The purpose of this paper is to provide the background context for the 29-30 September stakeholder consultation meeting, particularly with respect to how it relates to the ongoing deliberations of the Ad Hoc Open Ended Working Grou p to Enhance the Functioning of the MLS, and to highlight issues for discussion by participants during the stakeholder meeting.